Multidisciplinary Treatment of an Untreated Young Adult Patient with Unilateral Complete Cleft Lip and Palate - Aslan, Belma I.; Kucukkaraca, Ebru; Atac, Mustafa S.; Yildirim-Bicer, A. Zeynep; Ucuncu, Neslihan (Turkish journal of orthodontics, 2015)
We present the multidisciplinary treatment of a young adult patient with unilateral complete cleft lip and palate (UCLP). The patient with UCLP was 17 years old and had not applied for treatment before. He presented with a concave profile, lateral crossbite and a tete-a-tete overbite. After initial orthodontic treatment the patient’s cleft lip and nose and afterwards his palate were operated on. During the orthodontic treatment the patient had a negative overjet of 6 mm, a residuel fistule in soft palate, maxillary and secondary nose base deficiency, also a severe alveolar cleft in the premaxilla. To fix these problems, the patient’s maxilla was advanced by applying a Lefort-1 osteotomy, the secondary fistule in the soft palate was operated on and the alveolar defect was grafted with a biocollagen membrane, cansellous block graft and cansellous granular graft. The orthodontic treatment lasted 1 year following the orthognathic surgery. At the end of the orthodontic treatment Class I molar relationship was achieved on the right side and full Class II on the left side and also a 1 mm overjet and overbite. After a period of retention of 1.5 years some relapse occurred and delayed prosthetic treatment was performed by applying an adhesive bridge. Late term multidisciplinary treatment gave the UCLP patient a good appearance as well as psychological and social benefits.